Program of Russian art historians and training courses in this field - Alekseevna Sychenkova, Lydia (2021)
This paper reviews one of the first systematic programs in the history of art, developed in 1877 by P.V. Pavlov (1823 – 1895), professor of history at the University of St. Vladimir in Kiev. It is stressed that P. Pavlov’s program is a rare case of preserving the original curriculum of educational courses developed by Russian art historians of the 19th – early 20th centuries, which allows of its analysis within the framework of modern historical and cultural discourse. It is proved that the concept of the author of the program who stayed with his educational ideas ahead of the game in world science is unique. The article reveals the content of P. Pavlov’s synthetic approach to the consideration of all elements of spiritual culture, woven into the context of social history, intellectual currents, and the system of values. What calls attention to itself is the originality and innovation of P. V. Pavlov’s institutional ideas of establishing new departments of “history of fine arts and theory” and “history of artifacts” for in-depth studying and teaching of a wide range of historical and cultural disciplines. It is emphasized that a rethink of P.V. Pavlov’s program should become one of the steps towards reinterpretation of the history of Russian art criticism and contribute to the generation of new ideas in the system of history and art history education.  The suggestions about reprinting the program of P.V. Pavlov for discussion in the academic community of historians, cultural studies scholars and art historians are expressed. The proposed scholarly discussion around the propaedeutic heritage of art historians of the 19th – early 20th centuries should become one of the steps to prepare a new version of the history of Russian art criticism.